Fatigue Determines Work Motivation - Riska Rosita; Rahaju Muljo Wulandari; Pamela Hani Maretesia Putri; Sri Atun Amba Wani (Proceeding of International Conference on Science, Health, And Technology, 2019)
The hospital officer potentially experience fatigue caused by work, especially the medical records staff. Many of work less ergonomics, monotonous, and less rest time impact on work motivation. So needed research aimed at work know the effect of fatigue on work motivation on medical record officers at Dr. Arif Zainudin Hospital. This quantitative research uses the correlation method with cross sectional approach, population all medical records officers in Dr. Arif Zainudin Hospital. Research result show that age categories characteristics of respondents in the most 31-39 as much 41%, temporary employee status as much 54%, the highest level of education is diploma as much 59%, fatigue rates at medium level is 50%, and work motivation rates at a high level is 68%. Through fisher exact test shows that results p = 0.00 in significance 5%. The conclusion of this research there is a significant relationship between fatigue and work motivation on medical record officers at Dr. Arif Zainudin Hospital. Fatigue determines work motivation on medical record officers. The researcher's suggestion is that the hospital staffing department should redesign the work station, make variations in the work so that it is not static or monotonous, and provide sufficient rest time for the staff, so as to reduce the impact of work fatigue and increase the work motivation of the officers.